Wideband active antenna - A. Rahim, Mohamad Kamal (2003)
The objective of this work is to develop novel antenna designs for bandwidth enhancement using passive and active log periodic techniques. The first part of the thesis describes the integration of amplifiers with single microstrip patch antennas. The antennas have been designed at centre frequencies of 2.1 GHz and 2.6 GHz. There are four different configurations of the antenna and amplifier. The second part describes the passive log periodic technique. Antennas with different numbers of elements have been modelled using microstip lines and S parameter data from the single element. This data is extracted from the Momentum simulation and combined with the microstrip transmission line. The comparison between circuit and Momentum simulation shows very good agreement. The fabrication of the inset feed passive log periodic antenna has been done with four different numbers of elements: five, seven, nine and eleven. The centre frequencies of the antennas have been designed at 3 GHz with a bandwidth of 1.8 GHz for eleven elements LPA. The properties of the antennas such as bandwidth, gain, cross-polar isolation and half power beamwidth have been investigated and compared between different elements. The last part of the thesis is the integration of the amplifier with the log periodic antenna. The antennas have been designed with a bandwidth of 1 GHz with a centre fiequency of 3 GHz. Five different configurations have been investigated. The first configuration involves the integration of a single amplifier at the input of the feed line of a five element LPA. The , second configuration involves the integration of an amplifier in the middle of the five element LPA. The third configuration is a five element LPA with individual amplifiers in each element. In the fourth configuration, individual amplifiers and filters are integrated with five elements. The last configuration involves the integration of a single amplifier with a seven element LPA at the input to the feed line of the antenna The performance of these configurations have been investigated and compared in terms of bandwidth, gain relative to a passive LPA, cross polar isolation and beamwidth.